Analisis Pengaruh Kualitas Pembangunan Manusia, Pertumbuhan Ekonomi dan Pengangguran Terhadap Tingkat Kemiskinan di Kabupaten Keerom Tahun 2011 - 2021 - Maya Metapere; Elsyan R. Marlissa; Yundy Hafizrianda (Universitas Cenderawasih, 2023)
This study aims to analyze the effect of human development quality, economic growth, and unemployment on poverty levels in Keerom Regency during the period 2011–2021. The research employs a quantitative approach using path analysis based on secondary data obtained from Statistics Indonesia (BPS). The results show that economic growth has a significant effect on the Human Development Index (HDI), but does not have a significant effect on unemployment. Furthermore, both HDI and economic growth have a significant effect on poverty levels, while unemployment does not have a significant effect. Indirectly, economic growth also influences poverty through HDI as an intervening variable. These findings indicate that improving the quality of human development is a key factor in reducing poverty, therefore development policies should prioritize sustainable human resource development. Keywords: poverty, human development index, economic growth, unemployment